Expression of miR-210 in relation to other measures of hypoxia and prediction of benefit from hypoxia modification in patients with bladder cancer - Irlam-Jones, J J (Br J Cancer, 2016)
BACKGROUND: The addition of hypoxia modifiers carbogen and nicotinamide (CON) to radiotherapy (RT) improved overall survival (OS) in bladder cancer patients in the BCON phase III clinical trial. We investigate whether expression of hsa-miR-210 in BCON patient samples reflects hypoxia and predicts benefit from hypoxia modification. METHODS: In all, 183 T1–T4a bladder cancer samples were available for miR-210 analysis. A total of 86 received RT+CON and 97 received RT alone. TaqMan qPCR plates were used to assess miR-210 expression. Patients were classified as low (<median expression) or high (⩾median) miR-210. Data on other hypoxia biomarkers were available for comparison. RESULTS: Patients with high miR-210 had a trend towards improved 5-year OS with RT+CON (53.2%) compared with RT alone (37.8% hazard ratio (HR) 1.68, 95% CI 0.95–2.95, P=0.07). No benefit was seen with low miR-210 (HR 1.02, 95% CI 0.58–1.79, P=0.97). High miR-210 was significantly associated with high HIF-1α protein (P=0.001), CA9 protein (P=0.0004), Glut-1 protein (P=0.001), 26-gene hypoxia score (P=0.007), tumour necrosis (P=0.02) and concurrent pTis (P=0.03). CONCLUSIONS: High miR-210 may reflect hypoxia in bladder cancer. However, its ability to predict benefit from hypoxia modification does not improve upon other hypoxia markers. Investigation as part of a miRNA hypoxia signature may reveal the full potential of miR-210.